2023
DOI: 10.3389/fnut.2023.1190248
|View full text |Cite
|
Sign up to set email alerts
|

Kombucha tea as an anti-hyperglycemic agent in humans with diabetes – a randomized controlled pilot investigation

Chagai Mendelson,
Sabrina Sparkes,
Daniel J. Merenstein
et al.

Abstract: IntroductionKombucha is a popular fermented tea that has attracted considerable attention due, in part, to its suggested health benefits. Previous results from animal models led us to hypothesize kombucha may reduce blood sugar levels in humans with diabetes. The objective of this pilot clinical study was to evaluate kombucha for its anti-hyperglycemic activities in adults with diabetes mellitus type II.MethodsThe study was organized as a prospective randomized double-blinded crossover study at a single-center… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 60 publications
0
8
0
Order By: Relevance
“…Regarding the clinical assay from the USA of Mendelson, C., Sparkes, S., et al (2023) [24]. This clinical study they aimed to explore the potential antihyperglycemic effects of Kombucha in adults with type II diabetes mellitus (T2D).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding the clinical assay from the USA of Mendelson, C., Sparkes, S., et al (2023) [24]. This clinical study they aimed to explore the potential antihyperglycemic effects of Kombucha in adults with type II diabetes mellitus (T2D).…”
Section: Discussionmentioning
confidence: 99%
“…The trial of Vladimir Pilipenko [23] from Russia (2022) suggests specific improvements in IBS patients, so more research is needed in this field of study of the microbiota related to the benefits of consuming Kombucha. Concerning the two pilot clinical trials carried out in T2D and healthy individuals concerning Mendelson-Sparkes's research [24] and Atkinson Brand-Miller [25], the results are encouraging, reflecting the antidiabetogenic power demonstrated in animals, but with this small number of participants, it makes extrapolation of results difficult, so more clinical trials are necessary around diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…Although several efforts have been reported using synthetic bioactive products from chemical-based molecules, these bioactive products from chemical-based molecules have side effects that limit their usage. Interestingly, studies have shown that bioactive compounds synthesised via fermentation of biomass are safer with no side effects when compared with bioactive compounds from chemical-based molecules [ [5] , [6] , [7] , [8] ]. Apart from this, the bioactive products from the fermentation of biomass are environmentally friendly and affordable.…”
Section: Introductionmentioning
confidence: 99%
“…The addition of a wide range of nonclassical matrices, such as fruits, vegetables, plants and herbs, makes the variety of kombucha even richer (Barakat et al, 2022;Anantachoke et al, 2023;Wu et al, 2023). Kombucha is rich in tea polyphenols and organic acids, which have a variety of activities, such as antioxidant (Jakubczyk et al, 2020), liver protection (Moreira et al, 2022), antimicrobial (Nyiew et al, 2022;Vukic et al, 2023) and hypoglycemic (Mendelson et al, 2023) activities. A polysaccharide extract of novel shiitake mushroom kombucha was shown to have immunomodulatory effects (Sknepnek et al, 2021).…”
Section: Introductionmentioning
confidence: 99%